2001
DOI: 10.1016/s0029-7844(01)01580-0
|View full text |Cite
|
Sign up to set email alerts
|

Placenta percreta with spontaneous rupture of an unscarred uterus in the second trimester

Abstract: Spontaneous rupture of an unscarred uterus, due to placenta percreta, should be considered in cases of acute intraperitoneal hemorrhage, even in early pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 5 publications
0
22
0
5
Order By: Relevance
“…Patient 2 ' s request for termination of pregnancy was accepted by the Ethics Committee, in light of the extensive placental infi ltration, which was likely to deteriorate further with advancing pregnancy. Notably, several cases of uterine rupture and massive hemorrhaging have been reported for placenta percreta diagnosed at the beginning of the second trimester [3,12,14] .…”
Section: Discussionmentioning
confidence: 99%
“…Patient 2 ' s request for termination of pregnancy was accepted by the Ethics Committee, in light of the extensive placental infi ltration, which was likely to deteriorate further with advancing pregnancy. Notably, several cases of uterine rupture and massive hemorrhaging have been reported for placenta percreta diagnosed at the beginning of the second trimester [3,12,14] .…”
Section: Discussionmentioning
confidence: 99%
“…After previous cesarean section, the incidence varies between 0.4% and 0.9% [3,5] whereas in women without prior uterine surgery the incidence of uterine rupture is about 0.006%-0.02% [4,5]. In addition to previous cesarean section, postulated risk factors for uterine rupture are induction of labor, maternal age, multiparity, gestational age at delivery, vacuum-assisted birth, fetal birth weight, short inter pregnancy interval, prolonged second stage of labor, abnormal placentation, and uterine fundal pressure (UFP) [2,[6][7][8][9][10][11][12][13][14][15]. Although UFP is widely used [16] -a survey in the US found that in 80% of institutions UFP was applied [17] -there is scarce data about its' association with uterine rupture [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…8,9 The patient in this case report had no symptoms as discussed earlier except for ployhydramnios on presentation but later she developed antepartum hemorrhage and gross hematuria.…”
Section: Discussionmentioning
confidence: 58%